A gestão educacional no Paraná 2011-2013 - Sousa, Silmara Eliane de (2013)
From the 90s the intervention of international organizations in the state action, especially in the management of public policies has been strong. At this juncture the internationalization of the economy, relationships are established interests and policy options are materialized, resulting in changes in the way of implementing social policies. In this dynamic, education assumes the role of protagonist. Given this, the educational management is understood as the essential mechanism to ensure that the contradictions are ameliorated and the capital reproduces itself. Given the above, we analyze the educational policy of government management Beto Richa in the period 2011 to 2013, inquiring the confluence with the guidelines and directions of the World Bank present from the 90s in the State Reform in Brazil. According to the documents reviewed, the management Beto Richa has incorporated in his government, various political directions of the World Bank Group that were already present in the management Jaime Lerner (1994-2002), mainly in aspects related to the centrality of basic education and the quality management. The view of this, we organize our work into chapters to ensure the relationships that constituted the object of our analysis. Thus, in the first chapter we pointed out the willingness of the research. In the second chapter in view of the constitution of our analytical framework, we introduce the origin and the role of the State relating to democracy category to explain that educational management is an instrument of state power. In the third chapter, we pointed out the organization, operation and main directions of the World Bank, to celebrate the power of involvement of such organizations in Brazil, mainly from the reform of the Brazilian state. In the fourth chapter reiterate the assumptions of State Reform in Brazil linking them with the main mechanisms of educational management in government policy in Paraná Jaime Lerner. From the directions of the World Bank and correlations analyzed the Educational Management in government Beto Richa. Found in the research process that the government Beto Richa resumed more diligently and implicative policy design and referrals government Jaime Lerner already had the same elements of State Reform in Brazil, especially, correlate with the directions of the Bank Group World. The close linkage of these governments is due to the fact that both have committed financially and politically with this group. In addition, the two governments had a conception of state fully embedded in the liberal and market design advocated by these international bodies. Therefore, the educational management in government Beto Richa has constituted from a review of the theory of "Skills and Abilities and Shared Management" to become more elements through the guidance of the BM in the call management results